The Determinant Factor of Interest to Pay Zakat in Medan City Mosques Through Qris Using the Technology Acceptance Model (TAM) Approach - Lubis, Passa Sayyid Akbar; Rokan, Mustapa Khamal; Silalahi, Purnama Ramadani (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study explores various factors that influence people's interest in paying zakat, particularly those related to zakat knowledge, management transparency, service quality, and the level of religiosity. The research was conducted quantitatively in several mosques across Medan City, involving 60 selected respondents. Data were collected using a questionnaire and analyzed through multiple linear regression. The results of the study indicate that the variables of knowledge and perceived benefits have a positive and significant influence on the interest of zakat payers in paying zakat through QRIS at mosques in Medan City, while perceived risk has a negative but insignificant influence. Simultaneously, all three variables were found to have a positive and significant influence on the interest in using QRIS. These findings confirm that improving digital literacy and understanding the benefits of technology are the primary determinants in promoting the adoption of QRIS-based zakat payments in line with the Technology Acceptance Model (TAM) approach.